2021
DOI: 10.7202/1084452ar
|View full text |Cite
|
Sign up to set email alerts
|

Extending Medical Aid in Dying to Incompetent Patients: A Qualitative Descriptive Study of the Attitudes of People Living with Alzheimer’s Disease in Quebec

Abstract: Background: In Quebec, medical aid in dying (MAiD) is legal under certain conditions. Access is currently restricted to patients who are able to consent at the time of the act, which excludes most people with dementia at an advanced stage. However, recent legislative and political developments have opened the door to an extension of the legislation that could give them access to MAiD. Our study aimed to explore the attitudes of people with early-stage dementia toward MAiD should it become accessible to them. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Some years ago, Rurup et al (2006) reported that 89 per cent of 136 Dutch relatives of nursing home residents with dementia agreed that euthanasia should be accessible to 'incompetent patients if they signed an advance euthanasia directive when they were still competent'. High support for legalising advance requests for assistance in dying has also been found among persons with mild dementia (Thériault et al, 2021) and healthcare professionals (Tomlinson and Stott, 2015;Bravo et al, 2018bBravo et al, , 2018c.…”
Section: Attitudes Towards Maid For Persons With Dementiamentioning
confidence: 99%
“…Some years ago, Rurup et al (2006) reported that 89 per cent of 136 Dutch relatives of nursing home residents with dementia agreed that euthanasia should be accessible to 'incompetent patients if they signed an advance euthanasia directive when they were still competent'. High support for legalising advance requests for assistance in dying has also been found among persons with mild dementia (Thériault et al, 2021) and healthcare professionals (Tomlinson and Stott, 2015;Bravo et al, 2018bBravo et al, , 2018c.…”
Section: Attitudes Towards Maid For Persons With Dementiamentioning
confidence: 99%